Prospect of setting up a bottled water plant at Matang - Chang, Ignatius Yi Lee (Universiti Malaysia Sarawak (UNIMAS), 2001)
This research project paper investigates into the possibility for the Kuching Water Board to produce bottled water at its Matang Treatment plant i.e. value-added production into bottled water instead of only treated water. It touches on why the production of bottled water makes managerial and economic sense due to a continual demand for bottled water nationally and worldwide.